Bank loan contracting and corporate diversification: Does organizational structure matter to lenders? - Aivazian, Varouj A.; Qiu, Jiaping; Rahaman, Mohammad M. (Journal of financial intermediation, 2015)
This paper investigates the effect of corporate diversification on the pricing of bank-loan contracts. We find that diversified firms have significantly lower loan rates than comparable focused firms, and we find no evidence that diversified firms are subject to more restrictive non-price contract terms pertaining to maturity, collateral requirements, and covenant restrictions. We show that the effect of diversification on the cost of a bank loan is channeled primarily through coinsurance in investment opportunities and cash flows and that the effect is nonlinear: as the extent of corporate diversification grows, the cost-reduction benefit of diversification decreases. Our results indicate that the organizational structure of the firm can alleviate its external financing constraints and that it has an important bearing on the firm's financing capacity.